2015
DOI: 10.1007/s00540-015-1975-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine and propofol on sedation in patients after coronary artery bypass graft surgery in a fast-track recovery room setting

Abstract: Our results show that dexmedetomidine can easily be preferred over propofol in fast-track cardiac anesthesia due to its significant advantages of shorter extubation time and higher postoperative patient satisfaction scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 16 publications
0
46
0
3
Order By: Relevance
“…Further review of the abstract and full text of the remaining 91 articles was followed. At last, the final 18 RCTs [ 2 , 20 22 , 24 , 29 41 ] were included in this systematic review. Total of 1730 patients undergoing cardiac surgery were involved in these studies, including 865 cases in the dexmedetomidine group, and 865 cases in the control group (any treatment without dexmedetomidine).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further review of the abstract and full text of the remaining 91 articles was followed. At last, the final 18 RCTs [ 2 , 20 22 , 24 , 29 41 ] were included in this systematic review. Total of 1730 patients undergoing cardiac surgery were involved in these studies, including 865 cases in the dexmedetomidine group, and 865 cases in the control group (any treatment without dexmedetomidine).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 29 , 33 , 36 , 37 , 40 , 41 ] compared the rates of tachycardia of dexmedetomidine versus control (any treatment without dexmedetomidine) during surgery. There was no statistical heterogeneity (P = 0.91, I 2 = 0%) in each study, and a fixed effect model was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we found that time to discharge from the PACU tended to be lower in dexmedetomidine group compared to propofol group. In addition, Karaman et al demonstrated that the mean times to extubation were significantly lower in the dexmedetomidine group than in the propofol group in patients undergoing coronary artery bypass graft surgery. Further prospective studies are required to assess the discharge time from the hospital in dexmedetomidine propofol group.…”
Section: Discussionmentioning
confidence: 99%
“…As the safety of childhood anesthesia exposure in terms of neurodevelopment remains a highly controversial topic, the result of this meta-analysis has since been widely cited in the medical literature. At the writing of this editorial, six articles published in 2015 from Asian countries other than Japan [6][7][8][9][10] have been cited more than 5 times each. JA has thus served as a bridge between Asia and the global anesthesia community.…”
mentioning
confidence: 99%